Unusual case report of an intraspinal foreign body presenting as a meningocoele - Baranwal, Sunilkumar C; Saha, Suniti Kumar; Dasgupta, Sibaji; Sandeep, BV (Asian Journal of Medical Sciences, 2016)
Background: Non missile penetrating foreign body of the lumbo-sacral region presenting as a pseudomeningocele is an extremely rare condition. No significant data regarding this isavailable in our hand till date. We are reporting here a unique case of penetrating foreign body spine with pseudomeningocele presenting as lumbo-sacral swelling in a 1 ½ year old child. Case Description: A 1½ year male child presented with painless, low back midline swelling gradually increasing in size for 6 months. Swelling increased in size on crying and coughing. There was no external scar mark. Plain radiography revealed presence of a long slender radio-opaque foreign body in the spinal canal. Non- contrast computed tomography showed that the foreign body had penetrated the spinal canal at the level of L5 – S1 with a cystic space of CSF attenuation overlying it and extending into subcutaneous plane. Patient was explored through a transverse incision overlying the swelling. After opening the sac, the foreign body was found impacted between L5 and S1 lamina with CSF around the foreign body. The foreign body, a sewing needle was retrieved without disturbing its original trajectory. The narrow neck of sack was communicating with the spinal canal through a small dural defect which was closed and the sac was excised. Conclusion: A careful and meticulous approach is required from the surgeons point of view while taking a history, clinically assessing and performing surgery for patients presenting with acquired spinal swelling with such a unique etiology. Asian Journal of Medical Sciences Vol.7(4) 2016 94-97